Kitap sanatlarında vakvak üslûbu - Atilla, Oya (My University, 2016)
Tezyîni sanatlarda, en eski örneği 1000’li yıllara dayanan, doğuda Gazne’den batıda Mısır’a kadar geniş bir coğrafyada ve kitap sanatlarından mimari taş tezyinatına kadar, dokuma, cam, çini, metal, ahşap, kalemişi gibi bir çok sanat dalında kullanılan vakvak üslûbu, bezeme sanatının üslûplaştırmada geldiği üstün seviyeyi göstermektedir. Türk tezyini sanatlarında figüre yer verilmemesi fikrine karşın, oldukça özgün bir tavır sergileyen üslûp motifleri bulunduğu ortamın zengin kültür ortamının geniş hayal gücünün ürünüdür. Gerçek üstü bir anlayışın ve zengin bir tasvir gücünün ürünü olan üslûp motifleri insan, hayvan, hayali yaratık başları ve el motifinden ibarettir. Ender olarak vücutlarının bir kısmının veya tamamının da çizildiği bu motiflerin bir helezon üzerine yerleştirilerek kullanılmış olmaları üslûbun yegane özelliğidir. Motifleri ile dikkat çeken üslûbun bir helezona dahil olması klasik tezhip kompozisyon kurallarına uygun hale gelerek çeşitli desenlerin oluşturulmasına olanak sağlar. Kitap sanatlarında edebi ve ilmi yazma eserlerde kullanılan vakvak üslûbunun efsanevi vakvak ağacı ile yakın ilişkisi üslûbun bu ağaçtan türemiş olduğu fikrini güçlendirmektedir. Üslûbun tezyini sanatlarda kullanılan üslûpları anlatan 16.yüzyıla ait üç kaynakta da adının geçiyor olması önemlidir. “Kitap Sanatlarında Vakvak Üslûbu” isimli tez çalışmamızda amacımız, tezyîni sanatlarda yüzyıllar boyu sevilerek kullanılan vakvak üslûbunun tanıtılması ve konu üzerinde yapılacak yeni araştırmalara olanak sağlamaktır.

Vaqvaq style, origins of which could be traced back as early as early 1000s, that was utilized on a myriad of decorative art branches such as book illumination, architectural stone decoration, weaving, glassware, metalware, wood decoration, tiling, carving, and on a geography from Gazne on East to Egypt on West, shows the high level of sophistication the art of decoration has able to achieve. Despite the original thought that figures in general do not have a place in Turkish decorative arts, the highly original figures of this style are a byproduct of the strong power of imagination caused by the rich cultural environment. The figures of this style are the product of a surrealistic point of view and a very strong descriptive talent, and consist of heads of humans, animals, fictitious animals, and hands. Whole bodies are rarely shown, and the only common denominator of the various SUMMARY Vaqvaq style, origins of which could be traced back as early as early 1000s, that was utilized on a myriad of decorative art branches such as book illumination, architectural stone decoration, weaving, glassware, metalware, wood decoration, tiling, carving, and on a geography from Gazne on East to Egypt on West, shows the high level of sophistication the art of decoration has able to achieve. Despite the original thought that figures in general do not have a place in Turkish decorative arts, the highly original figures of this style are a byproduct of the strong power of imagination caused by the rich cultural environment. The figures of this style are the product of a surrealistic point of view and a very strong descriptive talent, and consist of heads of humans, animals, fictitious animals, and hands. Whole bodies are rarely shown, and the only common denominator of the various specimens of this style is that the figures are placed on a spiral. The inclusion of this decorative style in the body of aspirin allows it to fit classical ornamental rules, and allows it to compose different shapes. The vaqvaq style which is utilized in the book illumination, especially literary and scientific manuscripts, is in close similarity with the legend of the vaqvaq tree, supporting the idea that the style has been a derivative of that legendary tree. The fact that this particular style has been named on all three original sources dating to sixteenth century is also important. In this dissertation named Vaqvaq Style in Book Illumination, we aim to give information regarding this style that has been popular for centuries, and also to lay the groundwork for further research.
Keywords: El sanatları, Türk